Розвиток системи електронного документообігу управління персоналом (на прикладі Львівської міської ради) - Радзієвська, Ганна Русланівна; Radziievska, Hanna Ruslanivna (Національний університет "Львівська політехніка", 2023)
У сучасному інформаційному суспільстві ефективне управління персоналом є одним із основних факторів успіху будь-якої організації, в тому числі й органів місцевого самоврядування. Впровадження та розвиток систем електронного документообігу в управління персоналом є важливим кроком у напрямку оптимізації процесів, підвищення ефективності роботи та забезпечення прозорості діяльності. Актуальність теми обумовлена необхідністю вдосконалення існуючих систем електронного документообігу та моделей управління персоналом, зменшення витрат на обробку документів, підвищення якості умов роботи працівників та доступу громадян до публічних послуг. Об’єктом дослідження є офіс з управління персоналом Львівської міської ради. Предметом дослідження бакалаврської кваліфікаційної роботи є розвиток системи електронного документообігу управління персоналом. Метою дослідження є розроблення теоретичних та практичних рекомендацій щодо вдосконалення використання систем електронного документообігу в управлінні персоналом на прикладі Львівської міської ради та офісу з управління персоналом ЛМР. У першому розділі бакалаврської кваліфікаційної роботи проаналізовано теоретико-методологічні засади функціонування системи електронного документообігу, визначено перелік основних нормативно-правових актів, що регулюють їхню діяльність в Україні, окреслено роль систем електронного документообігу в кадровому менеджменті та узагальнено думки вітчизняних та закордонних дослідників щодо цих питань. У другому розділі проаналізовано динаміку та тенденції зміни основних фінансово-економічних показників діяльності офісу з управління персоналом Львівської міської ради. Сформовано перелік проблем функціонування систем електронного документообігу в контексті управління персоналом. У третьому розділі на основі закордонного досвіду та власного бачення запропоновано основні шляхи їхнього вирішення. У межах першого проєктного заходу запропоновано створення єдиної СЕД, а в межах другого — інтегрованої СЕД. Попри їхню схожість вони мають значні відмінності в питаннях автономії органів публічної влади та їхніх СЕД. Практичне значення запропонованих методів полягає в тому, що їхнє впровадження сприятиме підвищенню ефективності роботи офісу з управління персоналом Львівської міської ради та інших органів публічної влади, оптимізує процеси управління персоналом, покращить комунікацію та співпрацю між різними відділами та установами, забезпечить прозорість кадрових процесів та покращить доступ громадян до публічних послуг.

In today's information society, effective personnel management is one of the main factors in the success of any organization, including local governments. Implementation and developing of an electronic document flow system in personnel management is an important step towards optimizing processes, increasing work efficiency, and ensuring transparency. The bachelor's thesis is devoted to the study of the development of SE electronic document flow system in personnel management on the example of the Lviv City Council. The relevance of the topic is due to the need to improve existing electronic document management systems and personnel management models, reduce the cost of document processing, and improve the quality of working conditions for employees and citizens' access to public services. The object of research — personnel management office of the Lviv City Council. The subject of the research of the bachelor's qualification work is the development of the electronic document management system of personnel management. The purpose of the research is to develop theoretical and practical recommendations for improving the use of electronic document flow systems in personnel management for the example of the Lviv City Council and the personnel management office of the Lviv City Council. In the first chapter of the bachelor's qualification work, the theoretical and methodological principles of the functioning of the electronic document flow system were analyzed, the list of the main regulatory legal acts that regulate their activities in Ukraine was determined, the role of electronic document flow system in personnel management was outlined, and the opinions of domestic and foreign researchers on these issues were summarized. The second chapter analyzes the dynamics and trends of changes in the main financial and economic indicators of the activity of the personnel management office of the Lviv City Council. A list of problems of the functioning of electronic document flow systems in the context of personnel management has been formed. In the third chapter, based on foreign experience and our vision, the main ways to solve them are proposed. Within the framework of the first project proposal, the creation of a single electronic document flow system is proposed, and within the framework of the second - an integrated electronic document flow system. Despite their similarity, they have significant differences in terms of the autonomy of public authorities and their electronic document flow systems. The practical significance of the proposed methods lies in the fact that their implementation will contribute to improving the efficiency of the work of the personnel management office of the Lviv City Council and other public authorities, optimizing personnel management processes, improving communication and cooperation between different departments and institutions, ensuring the transparency of personnel processes and improving access of citizens to public services.
Development of the electronic document flow system of personnel management (on the example of the Lviv City Council)
Keywords: 6.281.00.00; — система електронного документообігу; електронний документообіг; цифровізація; IT-Enterprise; управління персоналом; орган місцевого самоврядування; офіс з управління персоналом; Львівська міська рада; - electronic document flow system; electronic document management; digitalization; IT-Enterprise; personnel management; local self-government body; personnel management office; Lviv City Council. List of used literature sources: 1. Kopnyak K. (2020). Electronic document management in public administration: problems of implementation; advantages; and prospects. Public administration: improvement and development; No. 10. 2. Kormyshkin Yu. (2021). Effective tools for personnel management in local self-government bodies. Bulletin of Agricultural Science of the Black Sea Region; No. 4. 3. Yarmystiy M. (2024). Motivation and improvement of the efficiency of civil servants. Public administration in the field of civil protection. 4. Shymchenko L. (2021). Electronic document management as an innovative mechanism for organizing public administration in the context of improving decentralization processes. Society. Document. Communication; No. 1(12). Smirnova Ya. (2023). Electronic document management in public authorities. Current issues of law and socio-economic relations